THE CRYSTAL CHEMISTRY OF LITHIUM IN THE ALLUAUDITE STRUCTURE: A STUDY OF THE (NA1-XLIX)1.5MN1.5FE1.5(PO4)3 SOLID SOLUTION (X = 0 TO 1) - Hatert F. (My University, 2004)
Phosphates of compositions (Na1-xLix)1.5Mn1.5Fe1.5(PO4)3 were synthesized by solid state reactions in air, and pure alluaudite-type compounds were obtained for x = 0.00, 0.25, and 0.50. Rietveld refinements of X-ray powder diffraction data indicate the occurrence of Mn2+ in the M(1) site, and of Fe3+ and Mn2+ in the M(2) site. For x = 0.25 and 0.50, A(1) is occupied by Li+ and Na+, whereas A(2)' is occupied by Na+ and vacancies. A careful examination of the number of electrons occurring in the A sites of the alluaudite-type compounds (Na1-xLix)MnFe2(PO4)3 and (Na1-xLix) CdIn2(PO4)3 confirms that lithium occupies only the A(1) crystallographic site of the alluaudite structure.
Keywords: alluaudite